The Changes in the Daily Activities Cycle of Women Informal Workers during the COVID-19 Pandemic: Vulnerability and Resilience - Asriani, Desintha Dwi; Fatimah, Dati; Mardhiyyah, Mida; Zubaedah, Aminatun (Sawwa: Jurnal Studi Gender, 2021)
Productive work is often identified with public work that generates money, even though productive work is work that has production value. This article is based on research discussing the daily activities cycle of women that work in the informal sector during the Pandemic of COVID-19 in Yogyakarta. The research method is qualitative, followed by gender perspective, to affirm the narrative based on women’s experiences and gender analysis. On one side, economic recession due to the Pandemic of COVID-19 has increased the vulnerability of women in the informal sector because their income depends on daily economic activity. Conversely, implementing social distancing has increased women’s workload at home. However, culturally, women’s works in private sectors such as care work and mothering, tend to be normalized. Economic activity is associated with men’s jobs as breadwinners and is limited to public space. Therefore, women seem unproductive economically despite endless work (at home). This article does not only explore one single aspect of women’s double burdens but discusses how women’s identical activity with care work has been disconnected from the economic cycle chain itself. Meanwhile, living during the COVID-19 pandemic time shows that women’s works become a vital pillar of resilience in handling health and economic crises. Therefore, it is important to reconstruct the meaning of productive roles from a gender perspective, namely roles that have production value both at the public and domestic levels.